Optimization of Teak Wood Furniture Production Using Linear Programming Method at Sumenep East Java Indonesia - Siti Nurul Afiyah; M. Syaifuddin; Nur Lailatul Aqromi; Darshil Makwana (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
3R Furniture company produces some products i.e. doors, chairs, cabinets, tables and frames. This company has some problems about maximize the production and minimize the cost of production. The 3R furniture company has not managed demand properly because it has not been able to synchronize the company's available resources with fulfilling consumer demand. This study aims to determine the amount of production produced by the